THE FORMATION OF AGGRESSION IN BEHAVIOR - BEHAVIOR OF PRESCHOOL CHILDREN - Saliyeva Dilorom Abdullayevna (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, the problem of aggressiveness is covered by Eastern and Western scientists and the issue of the specificity of aggressiveness in preschool children is reflected. At the same time, the causes of aggressiveness in children of kindergarten age have been studied by psychologists and their experimental analysis is presented.